EVALUASI PUPUK NITROGEN LEPAS LAMBAT PADA TANAMAN JAGUNG (Zea mays L.) - Agustina, Dwi Ulya; Rahman, Fahmi Arief; Supriyadi, Slamet; Wasonowati, Catur (Jurnal Tanah dan Sumberdaya Lahan, 2024)
Slow-release fertilizer can provide nutrients more efficiently; nutrients are released and available slowly so that they have the potential to be absorbed by plants. This study aimed to investigate the effects of several slow-release N fertilizers on the growth and yield of corn (Zea mays L.) in sandy soil. This research was carried out in the greenhouse and laboratory of the Faculty of Agriculture, University of Trunojoyo Madura. The experiment was arranged on a non-factorial completely randomized design. There were six treatment levels, namely P0 (uncoated urea fertilizer, applied into one application), P1 (uncoated urea fertilizer, split into three times applications), P2 (urea fertilizer with bentonite coating, P3 (urea fertilizer with biochar coating), P4 (urea fertilizer with coal coating), and P5 (urea fertilizer with biochar compost coating). All coated urea fertilizers were applied one time at the early growth of corn. The results showed that the application of slow-release N fertilizer had no significant effect on plant height, number of leaves, leaf area, cob length, diameter, plant fresh weight, plant dry weight, seed weight per plant, 100 seed weight, and flower age. However, the application of slow-release N fertilizer had a very significant effect on plant height at 42 DAP, the number of leaves at 14 DAP and 56 DAP, and leaf area at 28 DAP and 56 DAP. All coated urea fertilizers were as effective as uncoated urea on the growth and yield of corn.